Comparison of the subjective assessment of severity of pain during labor in various methods of pharmacological analgesia - Michalczyk, Michał; Torbé, Dorota; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Aim: To compare assessment of pain severity in the course of labor, according to the Visual Analogue Scale (VAS), in patients undergoing pharmacological anesthesia.Material and methods: The study included 128 pregnant women ≥ 37 weeks, who were delivered vaginally in the Department of Obstetrics and Gynecology of the Pomeranian Medical University in Szczecin in 2013-2017. The women were divided into four groups:1. PCEA (n = 33) women giving birth under patient-controlled epidural anesthesia (PCEA) in a horizontal position; 2. Pethidine (n = 24) women giving birth subjected to analgesia by parenteral supply of pethidine; 3. Fentanyl (n = 25) women giving birth subjected to analgesia by parenteral supply of fentanyl; 4. Control (n = 46) women giving birth without analgesia. During the first 24 hours after the delivery, a conversation with each patient was conducted, during which the method of describing pain intensity using the VAS scale was explained, and then the patient was asked to assess the perceived pain during labor.Results: Before application of any analgesia, pain was most strongly felt in the group of patients qualified for PCEA and pethidine anesthesia. In contrast, patients from the control group were characterized by statistically the lowest VAS score. After the application of a specified method of analgesia, there were also statistically significant differences in the perception of the severity of pain, which was the most strongly felt in the control group, while the lowest mean of VAS score was found in the group of patients anaesthetized by PCEA. Analysis of the difference between the VAS scoring values, before and after the application of analgesia (dVAS), showed that in the group of patients anaesthetized by PCEA, it was significantly the highest. There was also a statistically significant reduction in the severity of pain in the group of patients who were anaesthetized with PCEA.Conclusion: The use of epidural analgesia in the PCEA formula is characterized by the best effectiveness in relieving of labor pain among the analyzed methods.